Quranic understanding among non-native speaker of Arabic: Malaysian experts’ perspectives - Hazleena Baharun,; Saadah Abd Rahman,; Hishomudin Ahmad,; Noor Saazai Mat Saad,; Ikmal Hafiz Jamal, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The relationship between language and religion is complex and past studies have shown the importance of language and religion. In Islam, the most fundamental religious text that Muslims refer to is the Qur’an. Appreciating and understanding the Qur’an are fundamental for the believers of Islam to understand their religion. The Qur’an was revealed in the Arabic language. Hence, the aim of the study was two-pronged. One was to understand the importance of possessing knowledge of Arabic among non-native speakers of Arabic to understand the Qur’an and the other was to identify how non-native speakers of Arabic use the knowledge of Arabic to understand the Qur’an. The study employed exploratory design. A semi-structured interview method was used to collect data from five non-native speakers of Arabic. The collected interview data were analysed through thematic analysis. Results revealed that there was a need to have knowledge in Arabic to understand the Qur’an. Findings also showed that that non-native speakers of Arabic comprehend the Qur’an in three ways. One was using the translation approach; another was the lexical approach and the final one was using the linguistics approach. Thus, this has pedagogical implication. The teaching and learning to comprehend the Qur’an can be conducted in Arabic for specific purposes classes. The focus is on the Classical Arabic which encompasses the three approaches.